2021
DOI: 10.22605/rrh6471
|View full text |Cite
|
Sign up to set email alerts
|

Competencies for entry-level rural and remote physiotherapy practice: a Delphi approach

Abstract: Introduction: Rural physiotherapy is a challenging area of practice that requires clinicians to respond to the unique factors that contribute to rurality. This study aimed to outline an introductory set of competencies that contribute to effective physiotherapy practice in rural Australia. Methods: A three-round Delphi study was undertaken using a panel of expert physiotherapists. The panel was asked to provide open-ended responses to the following question: 'What unique knowledge, skills, abilities, attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The experts agreed regarding the importance of professional behaviour and the need to take responsibility for one’s own professional development (Items 3,4,5). Another study found similar results, concluding that all domains must be prioritised with regard to professional development and career progression (Martin et al, 2021a , b ). However, problems with the accessibility, availability and relevance of the content of CME programmes have been well documented as hindering physicians’ engagement (Yam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The experts agreed regarding the importance of professional behaviour and the need to take responsibility for one’s own professional development (Items 3,4,5). Another study found similar results, concluding that all domains must be prioritised with regard to professional development and career progression (Martin et al, 2021a , b ). However, problems with the accessibility, availability and relevance of the content of CME programmes have been well documented as hindering physicians’ engagement (Yam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 66%
“…The questionnaire contained a list of 9 attributes and 34 competencies (Table 1 ) that were separate from the required competencies listed in the document Indonesian Physicians’ Standard Competencies (Indonesian Medical Council, 2012 ). The proposed attributes and competencies were identified based on the literature (Australian College of Rural and Remote Medicine, 2021b ; Martin et al, 2021a , b ; Noya et al, 2021a ; Noya et al, 2021 ; Versteeg et al, 2013 ) as required for junior physicians to be able to work effectively in RR settings. This list was compared with existing curricula in Australia (Australian Rural Generalist Curriculum from the Australian College of Rural and Remote Medicine/ACRRM (Australian College of Rural and Remote Medicine, 2021b ) and the competencies required for entry-level Australian RR physiotherapy) (Martin et al, 2021a , b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6). 2 Preprofessional student placements in rural communities are known to increase student readiness for rural practice; 1,3 however, student preconceptions, 4 rural resource limitations, 5 and inadequate internal resources within universities 6 are known to limit placement opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…The need for clinicians to provide care that is responsive to these variables has been established in empirically derived competencies for effective rural physiotherapy practice, which include the ability to ‘ understand the unique social and occupational requirements for those living in a rural settin g’(pg. 6) 2 . Pre‐professional student placements in rural communities are known to increase student readiness for rural practice; 1,3 however, student preconceptions, 4 rural resource limitations, 5 and inadequate internal resources within universities 6 are known to limit placement opportunities.…”
Section: Introductionmentioning
confidence: 99%